2016
DOI: 10.1515/jtim-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Lipodystrophy HIV-related and FGF21: A new marker to follow the progression of lipodystrophy?

Abstract: Recently new evidence about fibroblast growth factor 21 (FGF21) highlights the opportunities to use this molecule in new pharmaceutical formulations to combat type 2 diabetes and metabolic syndrome. It is well known that HIV is per se a condition of insulin resistance and in particular the patient with HIV-related lipodystrophy has a condition strictly related to metabolic syndrome. Lipodystrophy is associated with severe metabolic side effects, including dyslipidemia, hepatic insulin resistance, and lipid oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The use of lean Fgf21-deleted mice (Fgf21-KO and Fgf21 liver KO) or Fgfr1 WAT KO mice has shown that Fgf21 limits lipotoxicity by reducing circulating FFAs and hepatic FA accumulation (Badman et al, 2007;Fisher et al, 2014;Yang et al, 2012). Recently, it was proposed that Fgf21-dependent improvement in serum FFAs and hepatic steatosis relies on a direct brain Fgf21 signaling (Benedini and Luzi, 2016;Nies et al, 2015). Our study supports this view, as we show that Fgf21 acts centrally to regulate lipid metabolism in scWAT and liver.…”
Section: Hypothalamic Fgf21 Is a Key Factor Participating In The Maintenance Of Whole-body Energy Homeostasissupporting
confidence: 88%
“…The use of lean Fgf21-deleted mice (Fgf21-KO and Fgf21 liver KO) or Fgfr1 WAT KO mice has shown that Fgf21 limits lipotoxicity by reducing circulating FFAs and hepatic FA accumulation (Badman et al, 2007;Fisher et al, 2014;Yang et al, 2012). Recently, it was proposed that Fgf21-dependent improvement in serum FFAs and hepatic steatosis relies on a direct brain Fgf21 signaling (Benedini and Luzi, 2016;Nies et al, 2015). Our study supports this view, as we show that Fgf21 acts centrally to regulate lipid metabolism in scWAT and liver.…”
Section: Hypothalamic Fgf21 Is a Key Factor Participating In The Maintenance Of Whole-body Energy Homeostasissupporting
confidence: 88%
“…In supporting this point of view, previous reports have shown significantly increased plasma FGF21 in lipodystrophy mice and humans as well as diabetic patients 64 , 65 . Furthermore, FGF21 plasma levels have been proposed as a marker for the following lipodystrophy in human immunodeficiency virus (HIV)-positive patients 66 .…”
Section: Discussionmentioning
confidence: 99%
“…The detection of a high FGF21 serum level in these patients was associated with MetS, lipodistrophy, and severe steatosis ( 239 241 ). Given the strong correlations between FGF21 and metabolic parameters, FGF21 has been suggested as a possible prognostic marker to monitor HALS and its therapy as well as the ART-associated cardiovascular risk ( 242 ). HIV infected patients also show high serum levels of resistin, an adipokine correlated with IR, lipoatrophy and NAFLD ( 243 ).…”
Section: Hiv and Hbv Role In Nafld Pathogenesis And In The Breakdown ...mentioning
confidence: 99%